2017
DOI: 10.1111/maec.12479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental variability on distribution and relative abundance of baleen whales (suborder Mysticeti) in the Gulf of California

Abstract: The Gulf of California (GC) is one of the most productive seas in the Pacific Ocean because of several oceanographic phenomena that support many marine mammal species, particularly of the cetacean order. The environmental variability of the GC was analysed during the cold and warm periods of 2005 and 2006 and its effects on the distribution and relative abundance of baleen whales using sea surface temperature (SST) and chlorophyll a (Chl a) concentration. Satellite image analysis allowed us to detect important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…What's more, Rhodobacteraceae and Alteromonadaceae had a strong oppositional correlation because Rhodobacteraceae was positively correlated with pH, Chl a and DAC, while Alteromonadaceae was negatively correlated with them. The result was also consistent with the report that Rhodobacteraceae could benefit from phytoplankton bloom and its relative abundance had a positive correlation with Chl a [40].…”
Section: Relationship Between Bacterial Community Composition and Envsupporting
confidence: 92%
See 2 more Smart Citations
“…What's more, Rhodobacteraceae and Alteromonadaceae had a strong oppositional correlation because Rhodobacteraceae was positively correlated with pH, Chl a and DAC, while Alteromonadaceae was negatively correlated with them. The result was also consistent with the report that Rhodobacteraceae could benefit from phytoplankton bloom and its relative abundance had a positive correlation with Chl a [40].…”
Section: Relationship Between Bacterial Community Composition and Envsupporting
confidence: 92%
“…Interestingly, the abundance of Alteromonadaceae increased and Rhodobacteraceae decreased during the lysis of algal cells. It has been reported that Rhodobacteraceae could benefit from phytoplankton bloom and its relative abundance had positive correlation with Chl a concentration [40]. Our results drew a similar conclusion, which showed that the density of algae cells and Chl a concentration reduces gradually during the algicidal process due to algae cell lysis (Table 1), and Rhodobacteraceae was positively correlated with Chl a and DAC (Fig.…”
Section: Variation Of Phycosphere Bacterial Community Of P Donghaiensesupporting
confidence: 86%
See 1 more Smart Citation
“…Nevárez-Martínez et al [54] obtained similar results when analyzing the distribution and abundance of the Pacific sardine (Sardinops sagax) in the Gulf of California, and its relationship with the environment, determining that the distribution is influenced by the SST and winds that causes upwelling effects. On the other hand, García-Morales et al [55] determined the influence of environmental variability in the distribution of whales in the Gulf of California, based on the SST and Chl a, they obtained that the largest number of whales were during the cold season of the Gulf of California and the lowest number during the warm season, concluding that the SST influence the relative abundance of the whales while the concentration of Chl a influences its distribution.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the influence of climatic indices and environmental variables on the encounter rate of humpback whales Spearman correlations were performed (Robinson et al, 2009;Garcıá-Morales et al, 2017).…”
Section: Climatic Indices and Environmental Variablesmentioning
confidence: 99%